Current advances in nanocarriers for biomedical research and their applications. (5th November 2018) - Rout, George Kerry; Shin, Han-Seung; Gouda, Sushanto; Sahoo, Sabuj; Das, Gitishree; Fraceto, Leonardo Fernandes; Patra, Jayanta Kumar
Abstract: Nanodrug delivery systems sometimes referred to as nanocarriers (NCs) are nanoengineered biocompatible materials or devices, which in conjugation with desired bioactive compounds plays an indispensable functional role in the field of pharmaceutical and allied sciences. The diversified ability of this bioengineered colloidal or noncolloidal molecule to breach the biological barriers to reach the targeted location in the biological system uplifts its other versatile natures of mono- or polydispersity in biodistribution. Furthermore, its nontoxicity and biodegradability result in making it a unique candidate for its purpose as drug delivery system. A number of different conjugations of chemical and biological substances are currently implemented for the synthesis of this biofunctional hybrid nanomaterial by simple methods. The use of these bioconjugated as a nanoparticulated system is currently being used for the treatment of various deadly incurable infectious diseases such as tuberculosis and disorders such as diabetes and cancers of various forms. Henceforth, the objective of the present review article is to provide overviews of the diversified and types of nanoparticulated systems, their beneficial as well as deleterious impacts along with the future prospect of nanodrug delivery system based on present status.